IMPROVING THE DIAGNOSIS OF INTRAUTERINE INFECTION IN NEWBORNS BASED ON THE ASSESSMENT OF THE CYTOKINE SYSTEM - Людмила Алексеевна Кривцова; Татьяна Николаевна Белкова; Татьяна Владимировна Оксеньчук; Мария Александровна Плеханова; Юлия Игоревна Тирская (The Publishing House Medicine and Enlightenment, 2020)
Currently, the problem of intrauterine infection (IUI) does not lose its relevance due to persistent peri- and postnatal losses, as well as the development of serious consequences in children, often leading to disability and a decrease in their quality of life. In this regard, it is important to study modern diagnostic criteria for intrauterine infection The aim of the research - to evaluate the diagnostic criteria for IUI in newborns from high-risk mothers based on the study of the cytokine profile. Materials and methods. 173 full-term and premature newborns were examined at birth and on the first or second day of life. The material for the study was cord blood, peripheral blood, CSF, tracheo-bronchial tree aspirate. Polymerase chain reaction (PCR) was used to determine the DNA of herpes simplex virus types 1 and 2, Epstein-Barr virus, cytomegalovirus, human herpes virus type 6, Toxoplasma, parvovirus, chlamydia, Mycoplasma, Ureaplasma. The determination of cytokines (tumor necrosis factor-alpha (TNF-α), interleukins (IL) - IL-1β, IL-6, IL-8, IL-10) and lactoferrin was performed by enzyme immunoassay (ELISA). Statistical processing was performed using the «STATISTIKA-6» application package, standard mathematical tables «Microsoft Excel». Results. When assessing the level of cytokines in the blood of newborns at high risk of developing IUI, it was proved that the implementation of IUI is accompanied by an increase in the content of proinflammatory cytokines IL-8, TNF-α in the blood of full-term newborns, a decrease in IL-1β and an increase in lactoferrin levels in premature newborns. Conclusion. On the basis of the obtained data, algorithms for diagnosis of IUI and management of newborns of different gestation periods are compiled.